2018
DOI: 10.5194/acp-18-3755-2018
|View full text |Cite
|
Sign up to set email alerts
|

The meteorology and chemistry of high nitrogen oxide concentrations in the stable boundary layer at the South Pole

Abstract: Published by Copernicus Publications on behalf of the European Geosciences Union. 3756 W. Neff et al.: The meteorology and chemistry of high nitrogen oxide concentrations in NO, whereas larger-scale features were associated with more moderate concentrations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The cognition of astronomical observation conditions was moved forward by the Italian and French Concordia "Dome C" station. The local topography of "Dome C" indicated that the surface wind speed should be lower and thus, the turbulent boundary layer should be confined closer to the surface [5,7]. These expectations have been confirmed by a series of site testing experiments operated over the last several years.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…The cognition of astronomical observation conditions was moved forward by the Italian and French Concordia "Dome C" station. The local topography of "Dome C" indicated that the surface wind speed should be lower and thus, the turbulent boundary layer should be confined closer to the surface [5,7]. These expectations have been confirmed by a series of site testing experiments operated over the last several years.…”
Section: Introductionmentioning
confidence: 73%
“…The expectation of weak free-atmosphere turbulence was also confirmed. A very strong turbulent surface layer, 200-300 m thick [6], was found, resulting in mediocre ground level seeing [7]. The cognition of astronomical observation conditions was moved forward by the Italian and French Concordia "Dome C" station.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, a stable polar vortex creates prime conditions for extensive cold periods by minimizing the intrusions of warm air into the continental (ice sheet) interior. Clear sky conditions augment the tendency towards low temperatures by increasing radiative cooling, and low wind speeds reduce mixing of boundary layer air, resulting in a strong surface inversion (Neff et al 2018;Keller et al 2022). Under strong inversion conditions, the mean wind direction at the South Pole is grid east/northeast (40°-80°; Neff et al 2018;Keller et al 2022), as air drains off the East Antarctic Plateau.…”
Section: S315mentioning
confidence: 99%
“…Clear sky conditions augment the tendency towards low temperatures by increasing radiative cooling, and low wind speeds reduce mixing of boundary layer air, resulting in a strong surface inversion (Neff et al 2018;Keller et al 2022). Under strong inversion conditions, the mean wind direction at the South Pole is grid east/northeast (40°-80°; Neff et al 2018;Keller et al 2022), as air drains off the East Antarctic Plateau. All of these factors were in play in 2021, resulting in a polar night that was substantially colder than average, although records were not set in any of the individual months.…”
Section: S315mentioning
confidence: 99%
“…), and atmospheric chemical properties including ozone and radical (e.g., OH, RO 2 and HO 2 ) concentrations are also needed to calculate the recycling of nitrate in the overlying atmosphere. In the model, the weekly air temperature and surface pressure were obtained from the Amundsen-Scott South Pole Station Meteorological Observations dataset (http://amrc.ssec.wisc.edu/usap/southpole/, last access: 12 October 2022), and the boundary layer height was set as 81 m, which is the mean observed value during November and December in 2003 (Neff et al, 2018). Surface ozone concentrations from 1975 to 2005 were obtained from the NOAA ozonesonde dataset (https://www.esrl.noaa.…”
Section: Transits Model Simulationsmentioning
confidence: 99%